2013
DOI: 10.1177/1352458513495580
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diagnostic criteria for neuromyelitis optica in patients with MS: a 10-year follow-up of the South Atlantic Project

Abstract: The frequency of NMO was 6.8% in São Paulo and 20.5% in Rio de Janeiro, and mainly seen in persons of African descent, which strengthens the hypothesis of there being an ethnic association of this disease. We recommend that epidemiological studies on MS that were performed previously be reviewed again, to ensure more accurate diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…Despite the lower frequency of AD studies, the majority of them showed a worse outcome in the AD group. It is worth noting that two studies did not exclude patients with the diagnosis of neuromyelitis optica 15,26 , a circumstance that may have caused bias, due to neuromyelitis optica being more common in AD than CA patients 32 and having a more severe course. Diverse risk factors for severe progression have been identified and extensively discussed in the literature; nevertheless, these results are not always consistent between studies, due to different classifications and methods of analysis, and genetic variability of the studied populations.…”
Section: In 1962 Alter Published the Research Results Of Ms Inmentioning
confidence: 99%
“…Despite the lower frequency of AD studies, the majority of them showed a worse outcome in the AD group. It is worth noting that two studies did not exclude patients with the diagnosis of neuromyelitis optica 15,26 , a circumstance that may have caused bias, due to neuromyelitis optica being more common in AD than CA patients 32 and having a more severe course. Diverse risk factors for severe progression have been identified and extensively discussed in the literature; nevertheless, these results are not always consistent between studies, due to different classifications and methods of analysis, and genetic variability of the studied populations.…”
Section: In 1962 Alter Published the Research Results Of Ms Inmentioning
confidence: 99%
“…The distribution of IIDD according to the new NMO and MS criteria has been investigated with regard to different populations. The results indicated the following relative frequencies of NMO cases among patients with MS: 1.2% in Australia [ 13 ], 1.5% in Italy [ 14 ], 8% in Mexico [ 15 ], 15.2% in southeastern Brazil [ 16 ], and 27% in Central America [ 17 ]. The highest frequency of cases featuring the selective involvement of the optic nerve and spinal cord s found in Japan, where 33% of patients with MS have Asian-type OSMS [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relative frequency of NMO to that of MS (NMO/MS ratio) was previously reported to be high in Thailand (1.4) [10] and Japan (0.29–0.59) [11,12], compared to that in Europe (0.024) [13] and Latin America (0.073–0.26) [14]. …”
Section: Introductionmentioning
confidence: 99%